Pengaruh Quick Response Indonesian Standard (Qris) dan Brand Awareness terhadap Loyalitas Pelanggan (Customer Loyalty) pada Chandra Superstore Lampung - Destiana; Handayani, Agustia; Wati, Ida (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2023)
ABSTRACT This study aims to test the effect of Qris and Brand Awareness on Customer Loyalty at Chandra Super Store Lampung. Loyalty is important for the running of a retail business. In order to fulfill customer desires, Chandra Super Store always does things that are competitive, creative, innovative and fast. Quantitative descriptive is the type of research used, through a survey method to obtain primary data sources and provide questionnaires for Super Store visitors. All Chandra Super Store customers are the population used in the study. The sample obtained was 92 respondents during the 3-day survey. The data analysis tool used is SPSS. The result is a Sign value.0.023 <0.05, meaning that Qris (X1) has a positive and sign effect on Customer Loyalty (Y). The easier Qris is to use in transactions, the more loyal customers will be to shop at Chandra Super Store. The Sign value.0.004 <0.05, meaning that Brand Awareness (X2) has a positive and sign effect on Customer Loyalty (Y). This means that the stronger and more people know about Chandra Super Store, the higher the level of customer loyalty. Keywords: Customer Loyalty, QRIS, Brand Awareness